2012
DOI: 10.1182/blood.v120.21.433.433
|View full text |Cite
|
Sign up to set email alerts
|

Gene Mutations and Treatment Outcome in Chronic Lymphocytic Leukemia: Results From the CLL8 Trial

Abstract: 433 Novel gene mutations have been found in CLL by next generation sequencing including mutations of NOTCH1 and SF3B1 in 5–20% of cases. In initial studies, both have been associated with advanced disease and poor outcome. We assessed the incidence and impact of gene mutations in the CLL8 trial (1st line FC vs. FCR, n=817). TP53 (exons 2–11) was analyzed by a re-sequencing chip (Amplichip, Roche Molecular Systems) with confirmatory Sanger sequencing. NOTCH1 was analyzed by Sanger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
131
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 0 publications
7
131
1
8
Order By: Relevance
“…CK was significantly associated with TP53 disruption, ATM deletions, del(6q), and IGHV UM status. Indeed, in univariate analysis, CK stood out as a significant poor prognosis marker both for PFS and OS and remained significant in multivariate analysis, together, as expected, with TP53 disruption and IGHV UM. No other molecular anomaly impacted survival, at variance from the CLL8 trial where NOTCH1 and SF3B1 carried a prognostic value …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…CK was significantly associated with TP53 disruption, ATM deletions, del(6q), and IGHV UM status. Indeed, in univariate analysis, CK stood out as a significant poor prognosis marker both for PFS and OS and remained significant in multivariate analysis, together, as expected, with TP53 disruption and IGHV UM. No other molecular anomaly impacted survival, at variance from the CLL8 trial where NOTCH1 and SF3B1 carried a prognostic value …”
Section: Discussionsupporting
confidence: 75%
“…Compared with first‐line therapy CLL studies, the cytogenetic and molecular defects observed in this cohort are at similar frequencies, except for SF3B1 mutations, much lower in our cohort. Of note, these data are different than reported in other studies, most likely because they included heterogeneous series of patients.…”
Section: Discussionsupporting
confidence: 58%
“…Among other biological poor risk factors, neither NOTCH1 nor SF3B1 mutations negatively impacted on ORR, PFS and OS, suggesting the effectiveness of alemtuzumab also in these genetic categories of patients. NOTCH1 mutations were slightly more frequent in the subgroup of patients that relapsed after fludarabine‐cyclophosphamide‐rituximab immunochemotherapy ( P = 0.07), which is consistent with the recently reported association between NOTCH1 mutations and the resistance to anti‐CD20 monoclonal antibodies .…”
Section: Discussionsupporting
confidence: 90%
“…Notably, among ibrutinib‐treated patients in the pooled analysis, del(11q) was associated with a trend of longer PFS and OS compared with those without del(11q). This is in contrast with standard first‐line CIT with fludarabine, cyclophosphamide, and rituximab, which has shown worse outcomes in patients with several high‐risk features . Together these data suggest that targeting intracellular B‐cell signaling by BTK inhibition with ibrutinib may be particularly beneficial in patients with features traditionally considered high‐risk, such as unmutated IGHV and del(11q), who may not be expected to respond well to standard CIT with fludarabine or bendamustine.…”
Section: Discussionmentioning
confidence: 98%